2005
DOI: 10.1111/j.0022-202x.2005.23919.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Heterogeneity of Erythrokeratoderma Variabilis

Abstract: The skin disease erythrokeratoderma variabilis (EKV) has been shown to be associated with mutations in GJB3 and GJB4 encoding connexin (Cx)31 and Cx30.3, respectively. Gap junctions composed of Cx proteins are intracellular channels providing a mechanism of synchronized cellular response facilitating metabolic and electronic functions of the cell. In the skin, Cx31 and Cx30.3 are expressed in the stratum granulosum of the epidermis with a suggested role in late keratinocyte differentiation. Molecular investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 27 publications
2
45
0
1
Order By: Relevance
“…Highly variable intrafamilial phenotypes were also noted, suggesting a strong influence of modifying genetic and epigenetic factors (2). Other studies also demonstrated that not all EKV cases harbour tnutations in Cx31 and Cx30.3 (14,15). Indeed, we could not find any hotspot mutations in members of this Chinese family.…”
Section: Discussionsupporting
confidence: 51%
“…Highly variable intrafamilial phenotypes were also noted, suggesting a strong influence of modifying genetic and epigenetic factors (2). Other studies also demonstrated that not all EKV cases harbour tnutations in Cx31 and Cx30.3 (14,15). Indeed, we could not find any hotspot mutations in members of this Chinese family.…”
Section: Discussionsupporting
confidence: 51%
“…Separating the two possibilities can be challenging but we have taken several factors into account when assessing the level of support of the original link. For example, lack of skin phenotype in the individual with LOF in GJB4 is likely due to incomplete penetrance, since this has previously been documented (Common et al 2005). Age-related penetrance represents another challenge as with the case that harbors a homozygous LOF in ZMYND15, which had been linked to spermatogenesis failure in adult males (Ayhan et al 2014).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The full-length coding region of drCx34.4 encompasses 900 bp and encodes a protein of 299 amino acids (aa). The ortholog genes in higher mammals are the connexin genes Cx30.3/31.1, genes with no known expression in the mammalian retina but profound correlation with erythrokeratodermia variabilis (EKV), a mostly autosomal dominant disorder of keratinization (Plantard et al 2003;Common et al 2005).…”
Section: Cloning Of Seven Novel Connexin Genes Expressed In the Adultmentioning
confidence: 99%